Context impact of clinical scenario on knowledge transfer and reasoning capacity in a medical problem-based learning curriculum. Issue 2 (3rd March 2016) - Collard, A.; Brédart, S.; Bourguignon, J.-P.
ABSTRACT: Since 2000, the faculty of Medicine at the University of Liège has integrated problem-based learning (PBL) seminars from year two to seven in its seven-year curriculum. The PBL approach has been developed to facilitate students' acquisition of reasoning capacity. This contextualized learning raises the question of the de- and re-contextualization process and its development during medical education. The aim is to assess transfer capacity of knowledge acquired through contextualized learning. A script concordance test (SCT) to assess clinical reasoning was administered to 104 volunteer students from year three to six of the Faculty of Medicine, and to a reference panel. The SCT has been created to measure, in a standardized way, reasoning capacity for ill-defined clinical problems. We used clinical cases from PBL seminars related to endocrinology from the third- and fifth-year (APP [Apprentissage Par Problèmes] and ARC [Apprentissage du Raisonnement Clinique] seminars). Two SCT scenarios aiming at the same learning objectives were created: one in the original learning context and one in a different, new context. Irrespective of the learning context, the reference panel showed higher scores than all groups of students. Students in year five and six obtained higher scores than younger students. A significant difference was also found in relation to the context (original/new) of the question. Higher scores were unexpectedly obtained for questions related to ARC cases than APP cases and in new contexts versus original ones, irrespective of the study level. The highest score was obtained for fifth-year cases in a new context. This study shows that from third year, students are able to transfer the knowledge acquired throughout PBL seminars for application to questions with information out of the learning context. Moreover, reasoning capacity grows with experience, irrespective of the process of transfer.